Quality of Working Life and Organizational Commitment of the Non-Commissioned Officers in the Engineer Department - เจษฎา พันตรี (Thai Interdisciplinary and Sustainability Review, 2019)
The research on the "quality of working life and organizational commitment of non-commissioned officers in the Engineer Department" aims 1) to study the quality of working life and organizational commitment of commissioned officers in The Engineering Department 2) to compare the quality of working life by personal factors of the non-commissioned officers in The Engineering Department. 3) to study the relationship between satisfaction in work, values and quality of working life of the non-commissioned officers in The Engineering Department 4) to study the relationship between the quality of working life and organizational commitment of the non-commissioned officers in the Engineer Department. The method is the quantitative research methods using the population and sample of the non-commissioned officers in the Engineer Department PANURANGSI Camp, which consists of 18 units. The statistics used in data analysis included 1) Descriptive Statistic using the Percentage, Mean, Standard Deviation to analyze and characterize individual factors, Economic dependence, Perception of political, society and technology, Political participation and Nationalist ideology, 2) Inferential Statistic used to analyze the relationship between the independent variables such as Individual factors , satisfaction in work and values and the dependent variables such as Quality of work life, organizational commitment by using t-test, One Way ANOVA (ANOVA Analysis), Pearson Product Moment Correlation Coefficient to explain and predict the influence of the factors variables which are consistent. For the study result, researchers found that most of the non-commissioned officers graduated from the Royal Military Academy. The average working time is 13 years, marital status is mostly married. Average monthly income is 15,000 baht and the average liabilities are about 234,068 baht and other obligations outside of the main tasks at intervals of 1 day per week. Satisfaction in working is at a high level. Pride in the profession is at a high level. Quality of working life is moderate and organizational commitment is moderate. The study found that relationship. Debt is associated with the quality of work life of commissioned officers in the Department of Sapper. Satisfaction in work is associated with the quality of work life in a positive medium. Pride in the professional relationship with the quality of work life in a positive medium. Quality of work life relationship with organizational commitment in a positive way rather high level.